Factors Influencing Organizational Performance in Metro Specialist Hospital, Sungai Petani, Kedah Darul Aman - Yasmin Musmuliana, Yatim Mustaffa (2012)
Organizations are commonly defined as instruments of propose.They are seen as coordinated by intentions and goals. Organizational performances in this way typically devote little attention to complications of using such formulation to characterize that the casual of performance phenomena. This study had concentrated on factor influencing organizational performance at Metro Specialist Hospital (MSH). The aims of the study are to examine the performance of the company and the most significant factors that influence the performance of MSH. The researcher had analysed four factor that influence organizational performance which is staff motivation, working environment, training and skill, and management involvement. A total of 100 questionnaires were distributed to 100 staffs at MSH by hand and only 82 questionnaires were returned for analysis. The data had been analysing by using Statistic Package for Social Sciences (SPSS). Research findings revealed there was significant relationship between working environment, training and skill, and management involvement with organizational performance. The multiple regression results had shown that the independent variable which is training and skill, and management involvement are a significant predictor for organizational performance.